Closing the loop: An evaluation of student-led module feedback at one UK higher education institution - Tschirhart, Cecile; Pratt-Adams, Simon David (International Journal for Students as Partners, 2019)
This article describes how a Student-Led Module Feedback (SLMF) scheme was initiated at one UK University to enhance staff-student relationships and to improve student outcomes. The scheme was developed by academics in partnership with the Students Union (SU) and students. The SLMF aimed to enhance the student experience at a granular level in “real time” during 30 week-long teaching modules. The article defines the SLMF within the research context of the Scholarship of Teaching and Learning and describes how the theme of student-staff partnership runs across the scheme, including during the project management and evaluation phases. It critically reflects on how the scheme has been instrumental in making inroads to improving the experience of students and staff across the university. It analyses the way in which the SLMF is being used by staff and students to co-create action plans to initiate pedagogical changes and thus close the loop of the feedback cycle.